Odpowiedź :
m1 - masa chłopca = 60 kg
v1 - prędkość chłopca = 8m/s
m2 - masa wózka = 40 kg
m1*v1 = m2*v2
v2 = (m1*v1)/m2
v2 = (480 kg*m/s)/40 kg
v2 = 12 m/s
Wózek porusza się z prędkością 12 m/s.
v1 - prędkość chłopca = 8m/s
m2 - masa wózka = 40 kg
m1*v1 = m2*v2
v2 = (m1*v1)/m2
v2 = (480 kg*m/s)/40 kg
v2 = 12 m/s
Wózek porusza się z prędkością 12 m/s.
m1=60kg
v1=8m/s
v2=om/s
m2=40kg
m1 x v1 + m2 x v2 = (m1+m2) x v
60kg x 8m/s + 40kg x Om/s =100kg x v
v = 60kg x 8m/s : 100 kg = 4.8 m/s
chyba ;d
v1=8m/s
v2=om/s
m2=40kg
m1 x v1 + m2 x v2 = (m1+m2) x v
60kg x 8m/s + 40kg x Om/s =100kg x v
v = 60kg x 8m/s : 100 kg = 4.8 m/s
chyba ;d